Teacher's professional agency – a relational approach to teacher learning. Issue 2 (2nd July 2016) - Pietarinen, Janne; Pyhältö, Kirsi; Soini, Tiina
ABSTRACT: The study aims to gain a better understanding of the complexity of teacher learning by exploring the elements of teachers' sense of professional agency in the two primary contexts of teachers' work: the professional community and the classroom. Moreover, the relationship with agentic learning in these contexts is studied. A total of 2310 primary and secondary school teachers completed the survey and the resulting data were analysed using structural equation modelling (SEM). The results confirmed that teacher learning in terms of professional agency is a complex and multi-dimensional phenomenon that cannot be reduced, and hence cannot be explained by a single behavioural attribute. The findings also indicated that the objects of learning and teachers' approaches to their learning determined the contextual variation in terms of professional agency. The results also showed that experienced agency in the classroom is dependent on teacher learning in the professional community. This implies that engaging teachers in learning outside their classrooms provides an effective strategy for improving instructional practices, and further, student learning.